A Scoping Review of Queer Paradox and Community in Online Spheres between 2015 and 2025 (Universitas Terbuka, 2025)
This study presents a systematic scoping review of research on queer paradox and community in online spheres published between 2015 and 2025. The review interrogates how digital platforms simultaneously function as emancipatory spaces that enhance queer visibility and as sites of surveillance, exclusion, and normative reproduction, thereby constituting the “queer paradox.” Guided by PRISMA protocols, 72 peer-reviewed articles were analyzed through thematic synthesis, focusing on the construction of queer identities, intersectional negotiations, and the dynamics of empowerment and oppression across digital environments. Findings reveal a significant growth of queer subculture scholarship, particularly in non-Western contexts, where digital technologies facilitate micro-communities that resist North-Atlantic paradigms of queerness. The review highlights three critical trends: the expansion of queer studies into diverse geographies, the predominance of qualitative methodologies such as thematic and discourse analysis, and the increasing scholarly attention to intersectionality, particularly regarding race, class, and gender modality. Nonetheless, the field remains constrained by methodological fragmentation, limited representation of transgender and nonbinary experiences, and Western dominance in knowledge production. This review underscores the necessity of interdisciplinary, context-sensitive approaches to theorizing digital queer cultures, with particular attention to ethical and political implications. By synthesizing empirical research across global contexts, the study contributes to developing more inclusive theoretical frameworks and provides directions for future scholarship, policy, and digital interventions aimed at fostering equitable queer participation in online spaces.